Trends in Italy's Nonprice Competitiveness - Lissovolik, Bogdan (IMF Working Papers; Working Paper ;, 2008)
Italy's medium-term economic performance has raised "standard" competitiveness concerns as unit labor costs surged, and real export growth fell. But the recent economic upturn, low current account deficit, and robust nominal exports argue for less pessimism. An empirical analysis confirms the standard concerns, but also suggests that "residual" factors, which partly reflect nonprice economic restructuring, have supported Italy's real exports after 2005 (as in Germany but less so in France or Spain). An investigation of selected structural trends over the past decade offers some substantiation to Italy's "restructuring story," including quality upgrading, geographical trade diversification, and outsourcing. But sluggish services, low FDI, and modest "technological" upgrading indicate limits to Italy's restructuring.